A comprehensive approach to therapy of haematological malignancies in older patients. Issue 11 (November 2021) - Cordoba, Raul; Eyre, Toby A; Klepin, Heidi D; Wildes, Tanya M; Goede, Valentin
Summary: Haematological malignancies are a heterogeneous group of diseases with diverse incidence. In Europe, the median age at diagnosis across all disease entities is 69 years. Incidence generally increases with age, reaching a maximum at 75–99 years, with the notable exceptions of Hodgkin lymphoma and acute lymphocytic leukaemia. Overall survival for patients aged 75 years and older with haematological malignancies is generally poor, particularly for acute leukaemias. Understanding the heterogeneity in outcomes for haematological malignancies, treatment challenges, and management of frailty and comorbidities among older patients could help physicians to better address the haematological cancer burden and mortality in ageing populations. The aim of this Series paper is to provide an updated overview of the knowledge accumulated over the past decade regarding treatment options and broader management considerations in older adults with haematological malignancies, focusing on the most common entities encountered across lymphoma, acute leukaemia, chronic leukaemia, and multiple myeloma disease categories. Future strategies, such as increasing enrolment rates of older adults in clinical trials and incorporating patient-reported outcome measurements in daily clinical practice, will assist in providing more individualised health care.